Analysis of Breast Cancer Radiation Dose Distribution Using Bolus Density in 3DCRT Technique Radiotherapy Planning at Andalas University Hospital - Dini Asetiyo; Dian Milvita; Muhammad Ilyas (Jurnal Ilmu Fisika, 2026)
Analysis of breast cancer radiation dose distribution using bolus density in radiotherapy planning of the Three-Dimensional Conformal Radiotherapy (3DCRT) technique has been conducted. This research aims to analyze radiation dose distribution in breast cancer patients using bolus density in radiotherapy planning of the 3DCRT technique. Five images of breast cancer patients were processed using TPS Eclipse software. The bolus density values used were a mixture of beeswax and petroleum jelly, playdough, silicone rubber, and 3D Polylactic Acid. CI and HI values were calculated based on the International Commission on Radiation Units and Measures (ICRU) Reports 62 and 83. Radiation dose in OAR was verified based on the Quantitative Analysis of Normal Tissue Effect in the Clinic (QUANTEC) standard. The results showed that all four bolus densities can be used in breast cancer patients, with CI values the CI value ranges from 0.93 to 0.98 by ICRU Report 62 standards and HI values close to ICRU Report 83 standards. In cardiac OAR, one patient exceeded the QUANTEC standard, while for lung OAR, all patients were below the QUANTEC standard. Using bolus density provides optimal radiation dose distribution on breast cancer targets.